Genome-wide analysis and expression profile of the bZIP transcription factor gene family in grapevine (Vitis vinifera) - Liu, Jinyi (BioMed Central, 2014)
BACKGROUND: Basic leucine zipper (bZIP) transcription factor gene family is one of the largest and most diverse families in plants. Current studies have shown that the bZIP proteins regulate numerous growth and developmental processes and biotic and abiotic stress responses. Nonetheless, knowledge concerning the specific expression patterns and evolutionary history of plant bZIP family members remains very limited. RESULTS: We identified 55 bZIP transcription factor-encoding genes in the grapevine (Vitis vinifera) genome, and divided them into 10 groups according to the phylogenetic relationship with those in Arabidopsis. The chromosome distribution and the collinearity analyses suggest that expansion of the grapevine bZIP (VvbZIP) transcription factor family was greatly contributed by the segment/chromosomal duplications, which may be associated with the grapevine genome fusion events. Nine intron/exon structural patterns within the bZIP domain and the additional conserved motifs were identified among all VvbZIP proteins, and showed a high group-specificity. The predicted specificities on DNA-binding domains indicated that some highly conserved amino acid residues exist across each major group in the tree of land plant life. The expression patterns of VvbZIP genes across the grapevine gene expression atlas, based on microarray technology, suggest that VvbZIP genes are involved in grapevine organ development, especially seed development. Expression analysis based on qRT-PCR indicated that VvbZIP genes are extensively involved in drought- and heat-responses, with possibly different mechanisms. CONCLUSIONS: The genome-wide identification, chromosome organization, gene structures, evolutionary and expression analyses of grapevine bZIP genes provide an overall insight of this gene family and their potential involvement in growth, development and stress responses. This will facilitate further research on the bZIP gene family regarding their evolutionary history and biological functions.